Pelatihan Penyusunan Laporan Keuangan Online sebagai Pemanfaatan Media Digital - Sutarni, Sutarni; Bria, Angela Merici; Syabila, Qoriah (Civiliza Publishing, 2024)
Giriloyo batik village is believed to have existed since the 17th century, during the reign of the Mataram Kingdom under the leadership of Sultan Agung. Initially, Giriloyo and his friends worked as batik instructors who sold half-finished batik to batik bosses in the center of Yogyakarta. The Giriloyo Batik Center is an area in Yogyakarta where the craft of hand-drawn batik has been passed down from generation to generation. Hundreds of generations of families in this area have made batik a part of their passion to preserve Indonesian cultural identity. Geographically, the Giriloyo Batik Center area is located in Ukirsasi Village, Imogiri District, Bantul Regency, Special Region of Yogyakarta (DIY) Province. This community service activity was motivated by the problems faced by Giriloyo Batik Village, namely the lack of literacy education related to digital-based financial reports, where the recording of financial reports that has been done so far is still manual and still uses or pays for the services of an accountant to create a financial report. So our team of proposers chose Kampung Batik Giriloyo to be a partner and we took the title